Systematic review of melatonin in cerebral ischemia-reperfusion injury: critical role and therapeutic opportunities - Zhang, Chenguang; Ma, Yumei; Zhao, Yating; Guo, Na; Han, Chen; Wu, Qian; Mu, Changqing; Zhang, Yue; Tan, Shutong; Zhang, Jian; Liu, Xu (Frontiers in Pharmacology, 2024)
Cerebral ischemia-reperfusion (I/R) injury is the predominant causes for the poor prognosis of ischemic stroke patients after reperfusion therapy. Currently, potent therapeutic interventions for cerebral I/R injury are still very limited. Melatonin, an endogenous hormone, was found to be valid in preventing I/R injury in a variety of organs. However, a systematic review covering all neuroprotective effects of melatonin in cerebral I/R injury has not been reported yet. Thus, we perform a comprehensive overview of the influence of melatonin on cerebral I/R injury by collecting all available literature exploring the latent effect of melatonin on cerebral I/R injury as well as ischemic stroke. In this systematic review, we outline the extensive scientific studies and summarize the beneficial functions of melatonin, including reducing infarct volume, decreasing brain edema, improving neurological functions and attenuating blood-brain barrier breakdown, as well as its key protective mechanisms on almost every aspect of cerebral I/R injury, including inhibiting oxidative stress, neuroinflammation, apoptosis, excessive autophagy, glutamate excitotoxicity and mitochondrial dysfunction. Subsequently, we also review the predictive and therapeutic implications of melatonin on ischemic stroke reported in clinical studies. We hope that our systematic review can provide the most comprehensive introduction of current advancements on melatonin in cerebral I/R injury and new insights into personalized diagnosis and treatment of ischemic stroke.